"What's Age Got to do With It, Got to do With It?" Midcareer College Teachers' Experiences in the Classroom. Issue 2 (3rd April 2019) - Bordt, Rebecca L.
Abstract: Based on a qualitative analysis of 38 interviews with midcareer professors at liberal arts colleges in the Midwest, this paper describes the teaching experiences of professors after 20-some years in the classroom. As a result of getting older and becoming more seasoned instructors, individuals cited an increase in their skill and efficiency in the classroom, better in-class performance, and more authority and respect among students. At the same time, respondents identified challenges that they viewed as unique to midcareer professors, including adjusting to a "new breed of students, " trying to hold on to the sacred classroom when institutional pressures pull them toward service and leadership, and balancing teaching with taking care of aging parents.